Earthworms (Amynthas spp.) increase common bean growth, microbial biomass, and soil respiration - Julierme Zimmer Barbosa (Semina: Ciências Agrárias, 2017)
Few studies have evaluated the effect of earthworms on plants and biological soil attributes, especially among legumes. The objective of this study was to evaluate the influence of earthworms ( Amynthas spp.) on growth in the common bean ( Phaseolus vulgaris L.) and on soil biological attributes. The experiment was conducted in a greenhouse using a completely randomized design with five treatments and eight repetitions. The treatments consisted of inoculation with five different quantities of earthworms of the genus Amynthas (0, 2, 4, 6, and 8 worms per pot). Each experimental unit consisted of a plastic pot containing 4 kg of soil and two common bean plants. The experiment was harvested 38 days after seedling emergence. Dry matter and plant height, soil respiration, microbial respiration, microbial biomass, and metabolic quotient were determined. Earthworm recovery in our study was high in number and mass, with all values above 91.6% and 89.1%, respectively. In addition, earthworm fresh biomass decreased only in the treatment that included eight earthworms per pot. The presence of earthworms increased the plant growth and improved soil biological properties, suggesting that agricultural practices that favor the presence of these organisms can be used to increase the production of common bean, and the increased soil CO 2 emission caused by the earthworms can be partially offset by the addition of common bean crop residues to the soil.